Sistem Audit Energi untuk Panel Surya dengan Logika Fuzzy - Yusril Ihza; I Wayan Agus Arimbawa; Wirarama Wedashwara (Journal of Computer Science and Informatics Engineering (J-Cosine), 2019)
Solar panels are alternative energy that utilizes the intensity of the sun as its energy source. The EBT (Renewable Energy) Laboratory of Electrical Engineering at the University of Mataram is currently still measuring conventionally using a multimeter. Measurements are carried out with the aim of recording the output of solar panels. It takes a tool to be able to measure the output of solar panels continuously and in realtime so that the energy obtained by solar panels can be known with certainty. The tool is made using a current sensor, voltage sensor, and temperature sensor and a microcontroller as a control to retrieve sensor data and then send it to the database using the MQTT protocol. Data on the database is presented in the form of a fuzzy database system and fuzzy queries are performed on the system. Data is collected from 08.00 to 17.00 for one week to get more accurate data. The measurement results and analysis will be displayed in the form of line diagrams with the WEB interface.